The Correlation Between Sleep Quality And Working Memory Using Forward And Backward Digit Span Test In Medical Faculty Students - Miftahul Raihan Alif; Ida Ratna Nurhidayati; Aya Yahya Maulana (Junior Medical Journal, 2022)
Background: Poor sleep quality is often found in medical students as a result of which many are not aware of due to academic loads and daily learning activities. Poor sleep quality can cause several factors, one of which is reduced working memory function. Working memory is the system whose role is to remember things when performing complex tasks such as reasoning, understanding, and learning. This study aims to determine the relationship between sleep quality and working memory in medical students.Methods This research was a cross-sectional analytic observational approach using purposive sampling as a way of determining the sample. The sample in this study was 41 respondents who were students of the YARSI University Medical Faculty class of 2019. The instruments were the Pittsburgh Sleep Quality Index to measure the respondent's sleep quality and the Digit Span Test to measure the respondent's working memory level. Bivariate analysis was performed using the Chi-Square test.Results: From the results of the analysis, it was found that 26 (63.4%) respondents had poor sleep quality and 32 (78%) respondents had moderate working memory. As many as 25 (78.1%) respondents had poor sleep quality with moderate working memory. The Chi-Square test results obtained a p-value of 0.000 (0.05) which indicates a significant relationship between sleep quality and working memory.Conclusion: There is a significant relationship between sleep quality and working memory in medical students. The advice that can be given is to maintain good sleep quality for optimal memory performance.